Analisis Filosofis Terhadap Peran Guru Dalam Pendidikan Karakter Di Sekolah Dasar - Nur Hasanah (Journal on Education, 2024)
Character education in elementary schools is a crucial aspect of forming individuals who are holistic, have integrity, and are ethical. This research employs a qualitative approach with in-depth interviews and direct observations of five teachers from various elementary schools to obtain rich and comprehensive data on how they implement character education in daily learning processes. The results show that the teachers have a profound philosophical awareness of the importance of character education. They not only teach moral values theoretically but also create an environment that allows students to experience and internalize these values through daily interactions. Various methods are used by the teachers, ranging from the integration of moral values into the curriculum, extracurricular activities, the use of moral stories, the habituation of positive attitudes, to class discussions and reflections. Although the methods used vary, all teachers demonstrate a strong commitment to integrating character education into every aspect of learning. This research confirms that the role of teachers in character education in elementary schools is very important and requires a deep approach and strong commitment. Character education should be seen as an integral part of education that is inseparable from the academic learning process. This research provides valuable insights into how character education can be effectively implemented in elementary schools and the importance of the teacher's role in this process.